Upaya Meningkatkan Keterampilan Passing Kaki dalam Melalui Model Kooperatif Jigsaw dalam Pembelajaran Sepak Bola - Muhammad Afif Nuruddin; Dony Andrijanto; Luthfi Aidin (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to investigate how to plan the learning process, the performance of teachers in its implementation, the improvement of students' basic passing skills in soccer, and student activity through the jigsaw technique. The research was conducted with fifth-grade students at SDN 1 Airlangga Surabaya. This is a classroom action research. Research instruments included observation sheets for lesson planning, teacher performance, student activity, learning outcome tests, field notes, and student interviews. The planning of learning showed improvement, with initial data at 52%, cycle I at 63%, cycle II at 78%, and cycle III at 100%, categorized as good. Teacher performance improved from an initial 47.22% to 69.58% in cycle I, 87.9% in cycle II, and 97.23% in cycle III, categorized as good. Student activity increased from an initial 12.8% (5 students) to 41% (16 students) in cycle I, 74.4% (29 students) in cycle II, and 97.4% (38 students) in cycle III, categorized as good. In learning outcomes, the initial data showed 17.9% (7 students), cycle I had 38.5% (15 students), cycle II increased to 76.9% (30 students), and cycle III reached nearly all students at 94.9% (37 students) achieving the passing standard. Thus, the jigsaw technique can enhance soccer passing learning for students.